Marcadores sedimentológicos, geoquímicos e micropaleontológicos no Quaternário tardio do talude continental da sub-bacia de Icaraí, bacia do Ceará, margem Equatorial brasileira - Noucoucouk, Agathe Arrissa (2020)
Sedimentological studies in deep marine environments are essential for understanding global climate changes and their projections for the future. This work investigates changes in the sedimentological, geochemical and micropaleontological composition of a core sample to understand the paleoceanographic and paleoclimatic variations that occurred during the Pleistocene-Holocene in the continental slope adjacent to the Ceará State coast, Brazilian Equatorial Margin. The following analyzes were performed: content of CaCO3; organic matter and organic carbon content; nitrogen and the C/N, Ti/Ca, Fe/Ca, Fe/K, Ti/Al ratios. Moreover, the micropaleontological content was performed using the planktonic and benthic foraminifera. The results of the micropaleontological analyzes were correlated to the general climatic changes occurring at regional and global scale. Biostratigraphic units were characterized based on the relative abundances of planktic foraminifera, indicators ofwarmand cold waters throughout the studied core. Two planktic foraminifera biozones were recognized: Y (late Pleistocene, glacial) and Z (Holocene, interglacial), and four subzones (Y2, Y1, Z2 and Z1). The Pulleniatina plexus allowed the division of zone Y in subzones Y2 and Y1 and the G. menardii plexus (G. menardii, G. tumida and G. fimbriata) allowed the division of zone Z in subzones Z2 and Z1. The sedimentary succession attributed to the Pleistocene was marked by high values of the Fe/Ca, Ti/Ca ratios, and, by the dominance of cold-water foraminiferal species. These results may suggest a drop of relative sea level with significant entry of terrestrial sediments. Whereas, the sedimentary succession attributed to the Holocene, was related to a constant influence of deep marine sedimentation with low values of Ti/Ca and Fe/Ca ratios and a dominance of warm water foraminifera species. Variations in the Ti/Ca, Fe/Ca ratios and the frequency of bioindicator of warm water speciesforaminifera, at the beginning of the Holocene, suggest a mobility to the north of the Intertropical Convergence Zone (ZCIT). The northernmost position of the ZCIT caused greater precipitation at the adjacent continent and the entry of a high volume of terrestrial sediments in the study area, which is related to the Heinrich I stage. The sedimentation rate in sub-area Y1 was estimated at 1.43 cm/ka and for the Z area at 7.45 cm/ka, which can characterize a depositional gap.